(untitled) (Jurnal PkM Pengabdian kepada Masyarakat, 2026)
Phonics is one of the subjects that pre-schools teachers need to teach. It is not easy to teach this subject since the text books do not provide how to pronounce the sounds. Phonetics facilitates the pre-school teachers who teach Phonics. Phonetics equips teachers with diagrams that presents what organs of speech are activated during the production of sounds. The community service program is to equip pre-school teachers with the sounds of bilabials, labiodentals, dentals, alveolars, and velars. The community service programs is conducted online using zoom platform and WAG. It comprises 14 sessions attended by 10 pre-school teachers. The training has three stages: teaching the class, demonstrating the sounds and assessment. The teachers are able to finish all the task given and are able to do the work individually and in group. In addition, they are given the opportunities to demonstrate how to pronounce the sounds learned in zoom room. They are drilled. They are assessed by pronouncing the words list and record all the production. After being equipped with Phonetics, they are expected to bring this knowledge when they teach their students. Therefore, the students can follow the lesson easily.